IJTIHAD POLITIK ISLAM PALEMBANG DI MASA ORDE BARU - Mikail, Kiki (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2018)
This research aims at exploring the dynamics of Islamic politics during Suharto’s New Order Regime, particularly when the regime simplifies political parties into merely three parties. This political shift, then, caused Muslim figures in Palembang, who were initially involved in Islamic political parties, to move their political vehicles and began to take a role in the management of Golkar party in one side, andremained consistent with the struggle of Islamic political parties in another side. This involvement was a middle ground for bridging the political interests of Muslims in Palembang and in the same time following the political flow of the central government.